2011
DOI: 10.1186/1471-2148-11-179
|View full text |Cite
|
Sign up to set email alerts
|

Variations on a theme: diversification of cuticular hydrocarbons in a clade of cactophilic Drosophila

Abstract: BackgroundWe characterized variation and chemical composition of epicuticular hydrocarbons (CHCs) in the seven species of the Drosophila buzzatii cluster with gas chromatography/mass spectrometry. Despite the critical role of CHCs in providing resistance to desiccation and involvement in communication, such as courtship behavior, mating, and aggregation, few studies have investigated how CHC profiles evolve within and between species in a phylogenetic context. We analyzed quantitative differences in CHC profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 90 publications
0
42
0
6
Order By: Relevance
“…This pattern of speciational change has also been found for the macro evolution of Timema courtship behavior, but not for the macroevolution of male genitalic morphology, which has diversified in proportion to phyletic branch lengths, apparently under forces of sexual selection or sexual conflict [52]. Among other insect species, previous studies of macroevolutionary change in hydrocarbon profiles have reported rapid evolution in conjunction with species specificity and a notable degree of phylogenetic conservatism [50,53,54], patterns that are largely concordant with those described here for Timema , but have not been partitioned into speciational versus phyletic concentrations of change. If changes in cuticular hydrocarbon profile drive speciation, then directional selection due to mate choice with profile-based criteria should characterize processes of divergence or reinforcement, while stabilizing selection should predominate at other times.…”
Section: Discussionmentioning
confidence: 76%
“…This pattern of speciational change has also been found for the macro evolution of Timema courtship behavior, but not for the macroevolution of male genitalic morphology, which has diversified in proportion to phyletic branch lengths, apparently under forces of sexual selection or sexual conflict [52]. Among other insect species, previous studies of macroevolutionary change in hydrocarbon profiles have reported rapid evolution in conjunction with species specificity and a notable degree of phylogenetic conservatism [50,53,54], patterns that are largely concordant with those described here for Timema , but have not been partitioned into speciational versus phyletic concentrations of change. If changes in cuticular hydrocarbon profile drive speciation, then directional selection due to mate choice with profile-based criteria should characterize processes of divergence or reinforcement, while stabilizing selection should predominate at other times.…”
Section: Discussionmentioning
confidence: 76%
“…() and Oliveira et al . (): D. serido , [( D. gouveai , ( D. seriema , D. borborema )]. The geometric mean of the population mutation rate (θ = 4Nu) of the independent loci was used to estimate priors for population size and migration rate parameters, as suggested in the IMa2 manual.…”
Section: Methodsmentioning
confidence: 99%
“…Although modelling abiotic conditions, such as temperature and precipitation, should be regional enough to make conclusions valid, we have not considered confounds from species that could have been sampled from microclimates. For instance, arid species, such as D. buzzatii, have been collected from arid corridors of otherwise tropical areas of Brazil (Oliveira et al, 2011); thus pressures concerning water and precipitation will be different than in arid areas adjacent to temperate regions. This highlights the difficulties in making generalizations, even within a species, and underscores the need to record where and under what conditions the samples are acquired in any study.…”
Section: Broader Perspectives and Conclusionmentioning
confidence: 99%